2009
DOI: 10.1007/s11420-008-9104-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diffuse Pigmented Villonodular Synovitis of the Knee with Combined Surgical and Radiosynovectomy

Abstract: Treatment of extensive diffuse pigmented villonodular synovitis (PVNS) of large joints by isolated surgical resection is unsatisfactory, with high rates of local recurrence. Post-synovectomy adjuvant treatment with external beam radiation therapy or intra-articular injection of radioactive material as yttrium-90 ( 90 Y) yielded better results. Between January 2005 and January 2007, 12 patients (eight men and four women aged 19-49 years) with extensive diffuse PVNS of the knee were treated. All patients had an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 12 publications
2
45
1
4
Order By: Relevance
“…No complications of surgery or RT were recorded. The functional outcome of the involved joint in all patients was good according to Enneking's criteria (postoperative score 85%) [30].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…No complications of surgery or RT were recorded. The functional outcome of the involved joint in all patients was good according to Enneking's criteria (postoperative score 85%) [30].…”
Section: Discussionmentioning
confidence: 87%
“…Several recent publications showed favorable effect of external beam RT as a postoperative treatment [11,12,18,[28][29][30][31]. The GCG-BD group conducted a pattern-of-care study to analyze the RT for PVNS [12].…”
Section: Discussionmentioning
confidence: 99%
“…Of nine patients in the series, eight were disease free and one had local recurrence [18]. Nassar et al used external beam radiotherapy after debulking surgery and reported no disease recurrence or progression of bone or articular destruction in any patient, nor any complication related to the surgical procedure or radiotherapy [19].…”
Section: Discussionmentioning
confidence: 93%
“…The numerous papers show significant improvement of efficacy of RS [3][4][5][6][7][8][9][10]. This method was first used in 1952 in patients with rheumatoid arthritis [11].…”
Section: Introductionmentioning
confidence: 99%